Effect of L-NAME on the Synthesis of Plasma Fibrinogen in Mice - Yasutaka Takinishi; Masako Okazaki; Katsuji Oguchi (Elsevier, 2005)
The effect of nitric oxide (NO) on plasma fibrinogen was investigated by treating mice with oral NG-nitro-L-arginine-methyl ester (L-NAME), a non-selective NO synthase (NOS) inhibitor. Treatment with L-NAME significantly increased the concentration of plasma fibrinogen and hepatic expression of the α- and β-chains of fibrinogen, whereas plasma NO2− level and hepatic expression of endothelial NOS (eNOS) mRNA were significantly decreased. These results suggest that L-NAME treatment can increase plasma fibrinogen levels via an increase in expression of fibrinogen mRNA in the liver, and NO may be involved in plasma fibrinogen increase. Keywords:: fibrinogen, NG-nitro-L-arginine-methyl ester, mRNA